2008
DOI: 10.1007/s12020-008-9044-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of metabolic syndrome and associated risk factors among Turkish adults: Trabzon MetS study

Abstract: MetS is moderately common and an important health problem in the adult population of Trabzon. In order to control MetS and its components, effective public health education and taking urgent steps are needed. These steps include serious education, providing a well-balanced diet and increasing physical activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
37
2
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 46 publications
(100 reference statements)
13
37
2
8
Order By: Relevance
“…Age is well accepted to be one of the strongest predictor of metabolic syndrome in the general population (Riediger and Clara, 2011). This finding is consistent with those of other studies carried out in Korea as well as worldwide (Ford et al, 2002;Park et al, 2004;Erem et al, 2008;Mohamud et al, 2011;Rodrigues et al, 2013 ). This association is due to the inevitable physiological processes of aging, such as declining basal metabolic rate, changes in body composition, and unhealthy lifestyle (Bechtold et al, 2006).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Age is well accepted to be one of the strongest predictor of metabolic syndrome in the general population (Riediger and Clara, 2011). This finding is consistent with those of other studies carried out in Korea as well as worldwide (Ford et al, 2002;Park et al, 2004;Erem et al, 2008;Mohamud et al, 2011;Rodrigues et al, 2013 ). This association is due to the inevitable physiological processes of aging, such as declining basal metabolic rate, changes in body composition, and unhealthy lifestyle (Bechtold et al, 2006).…”
Section: Discussionsupporting
confidence: 87%
“…There can be an increasing prevalence for metabolic syndrome in the near future due to the increasing trend of breast and colon cancer and the decreasing trend of gastric cancer in Korea (Jung et al, 2011). General risk factors for metabolic syndrome are female, old age, high BMI, current smoking status, heavy alcohol consumption, inadequate physical activity and low socio-economic level (Park et al, 2004;Erem et al, 2008;Mohamud et al, 2011;Rodrigues et al, 2013). In our study, only 2 risk factors (age and BMI) among many variables showed a significant association with metabolic syndrome in cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
“…22 Studies investigating prevalence of MetS in general Turkish population showed heterogeneous results. 31 and found a MetS prevalence of 26.9% in people aged 20 and above according to ATP-III, 31.3% in females and 21.7% in males. Comparing our results with this study, based on the similarity of the geographical region, gives an odds ratio of 1.33, which indicates a slightly increased risk of MetS among the people with SMIs.…”
Section: Discussionmentioning
confidence: 98%
“…Most of the evidence regarding socio-economic and lifestyle determinants of MetS have come from American (9)(10)(11)(12) and Asiatic settings (13,14) and from southern European countries (15,16) . However, these findings were inconsistent owing to diversity in the populations' characteristics, the criteria used to define MetS, the methodologies of data collection and the selection of confounding factors.…”
mentioning
confidence: 99%